4‐Aminoquinoline‐β‐Lactam Conjugates: Synthesis, Antimalarial, and Antitubercular Evaluation. (28th October 2013) - Raj, Raghu; Biot, Christophe; Carrère‐Kremer, Séverine; Kremer, Laurent; Guérardel, Yann; Gut, Jiri; Rosenthal, Philip J.; Kumar, Vipan
<x xml:space="preserve">Abstract</x> A library of quinoline‐β‐lactam‐based hybrids was synthesized and tested for their antimalarial and antitubercular activities. The present antimalarial data showed the dependence of activity on the nature of linker, N‐1 substituent of the β‐lactam ring as well as the length of alkyl chain. Most of the compounds are not as efficient as chloroquine in inhibiting the culture growth of Plasmodium falciparum W2 strain. Nevertheless, the synthesized hybrids showed better antitubercular activities (up to five times) compared with cephalexin (up to three times) and ethionamide.